(3UahI GdUaGJ aj TQM OYGA GdSeGJs - (3GdcaYej, , Jbj GdOjf, GdcaYej, EHQGgje Hf Ydj Hf GdMSf GdMGQKj GdYGedj, J (B905(3g` (B1500(3es ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj G,Wb CdSJfG HdZI GdYQH GdYQHGA haVd HgG fMGQjQ GdYdeGA heUGbY GdHdZGA hLYdgG aj GdChdjjf dHjGf aQbGfgs
(3BNQgG (B:s
(3BNQgG(B: (3hGdeSFhd ef NdGf GdUaG hENhGf GdhaG Ef QCh ehLHI Sgh SJQhgG Ch LGQjI YjH NahgG Ch gahI dSGf (B.. (3SOhgG aJdc YGOI NdUGA (B.., (3hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B1: 54s
(3GdPQjYI, L (B18: 37s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs